Взаємопов’язаність правочинів як окрема ознака значного правочину господарського товариства - Лантінов, Ю. Ф.; Lantinov, Yu. F. (Право і безпека. - 2014. - № 1 (52). - С. 139-144, 2014)
З’ясовано поняття та ознаки взаємопов’язаності декількох правочинів як одну з ознак значного правочину господарського товариства. Досліджено ознаки взаємопов’язаних правочинів, що закріплені в іноземному законодавстві, судовій практиці іноземних держав та у науці корпоративного права. Запропоновано розрізняти суб’єктивні та об’єктивні (в тому числі цільові, предметні та часові) ознаки взаємопов’язаних правочинів. Надано характеристику таких ознак та сформульовано доктринальне визначення взаємопов’язаних правочинів.

Most foreign regulations classify a major transaction as a number of transactions if they are interrelated to each other. Considering this fact the article is devoted to the ascertainment of the notion and features of some transactions’ interrelatedness as one of the features of a business entity’s major transaction. Features of interrelated transactions, set forth in the foreign legislation, judicial practice of foreign countries and in science of corporate right, are researched. Among the features the author singles out: uniformity of transactions, limitation in time, the unity of the property, which is the subject of transactions, the unity of purpose of transactions, coherence of corresponding subjects between each other, etc. The author of the article offered to distinguish subjective and objective features of interrelated transactions. In turn it is suggested to distinguish target, subject and time elements among objective features. Characteristic of such features is conducted and the doctrinal definition of interrelated transactions is formulated. It is offered to consider several (two or more) single-type transactions as interrelated, which are executed by a business entity with several affiliated with each other subjects, which are aimed at achieving a common goal and led (lead) to general legal consequences in the form of alienation (possibility of alienation) or property’s acquisition, where the subject is divisible things or other objects of property rights, which are uniform and in the aggregate have an integrated functional purpose (except an individual property right, service or work not related to the creation of a new thing), as well as aggregate of objects that compose a complex thing (integral property complex) if transactions are executed simultaneously or within a small period of time that makes it possible or leads to the subsequent use of objects of such transactions as a whole.

Выяснены понятие и признаки взаимосвязанности нескольких сделок как одного из признаков крупной сделки хозяйственного общества. Исследованы признаки взаимосвязанных сделок, закреплённые в иностранном законодательстве, судебной практике иностранных государств и в науке корпоративного права. Предложено различать субъективные и объективные (в том числе целевые, предметные и временные) признаки взаимосвязанных сделок. Дана характеристика таких признаков и сформулировано доктринальное определение взаимосвязанных сделок.
Interrelatedness of transactions as a single feature of a major transaction of a business entity
Взаимосвязанность сделок как отдельный признак крупной сделки хозяйственного общества
Keywords: господарське товариство; значний правочин; взаємопов’язані правочини; суб’єктивні ознаки; об’єктивні ознаки; business entity; major transaction; interrelated transactions; subjective features of interrelated transactions; objective features of interrelated transactions; хозяйственное общество; крупная сделка; взаимосвязанные сделки; субъективные признаки; объективные признаки